Soft Computing in Computer and Information Science - Wiliński, Antoni (Springer, 2015)
This book presents a carefully selected and reviewed collection of papers presented during the 19th Advanced Computer Systems conference ACS-2014. The Advanced Computer Systems conference concentrated from its beginning on methods and algorithms of artificial intelligence. Further future brought new areas of interest concerning technical informatics related to soft computing and some more technological aspects of computer science such as multimedia and computer graphics, software engineering, web systems, information security and safety or project management. These topics are represented in the present book under the categories Artificial Intelligence, Design of Information and Multimedia Systems, Information Technology Security and Software Technologies.